Factors associated with intrapartum stillbirth in a tertiary teaching hospital in Burkina Faso - Bewendin Evelyne Komboigo; Bewendin Evelyne Komboigo; Hyacinthe Zamane; Hyacinthe Zamane; Abou Coulibaly; Sansan Rodrigue Sib; Madina Thiombiano; Blandine Thieba; Blandine Thieba (Frontiers Media S.A., 2023)
IntroductionIntrapartum stillbirth is an indicator of health and community development.ObjectiveTo identify the risk factors associated with intrapartum stillbirth in a tertiary teaching hospital in Burkina Faso.Patients and methodsA case-control study conducted from January 1 to August 30, 2019. Cases were defined as patients admitted to Yalgado Ouedraogo teaching hospital (YOTH) with a live fetus of at least 28 weeks' gestation and who gave birth to an intrapartum stillborn, a fetus delivered without any signs of life in the first minute postpartum. Controls were defined as patients who delivered a live newborn. Study controls were gradually recruited and matched to cases. For each case, two controls were recruited and matched according to criteria such as delivery route and day of delivery. Data were cleaned in Epidata and exported to Stata for analysis. Variables with a p < 0.05 significance level in the multivariable regression were retained. Odds ratio (OR) and 95% confidence intervals are reported.ResultsEighty-three intrapartum stillbirths were documented among a total of 4,122 deliveries, a stillbirth rate of 20.1 per 1,000 births. There was a statistically significant association between intrapartum stillbirth and prior caesarean section (p = 0.045), multiparity (p = 0.03), the receipt of antenatal care (ANC) by a nurse (p = 0.005) and the disuse of the partogram (p = 0.004). We did not find a significant association between the number of ANC consultations performed (p = 0.3), whether membranes were ruptured at admission (p = 0.6), the duration of labor (p = 0.6) and intrapartum fetal death. Multivariate analysis showed that patient referral to another heath facility (OR: 3.33; 95% IC: 1.56, 7.10), no obstetric ultrasound performed (OR: 3.16; 95% IC: 2.11, 4.73), birth weight less than 2,500 g (OR: 7.49; 95% IC: 6.40, 8.76) were significantly associated with intrapartum stillbirth.ConclusionSpecific interventions must be taken to identify these risk factors of intrapartum stillbirth in order to ensure better and appropriate management.